Comparative Genomics, Whole-Genome Re-sequencing and Expression Profile Analysis of Nucleobase:Cation Symporter 2 (NCS2) Genes in Maize - Chai, Wenbo; Peng, Xiaojian; Liu, Bin; Wang, Jing; Zhu, Zhan; Liu, Yin; Zhao, Kai; Cheng, Beijiu; Si, Weina; Jiang, Haiyang (Frontiers in Plant Science, 2018)
Nucleobase:cation symporter 2 (NCS2) proteins are important for the transport of free nucleobases, participating in diverse plant growth and developmental processes, as well as response to abiotic stress. To date, a comprehensive analysis of the NCS2 gene family has not been performed in maize. In this study, we conducted a comparative genomics analysis of NCS2 genes in 28 plant species, ranging from aquatic algae to land plants, concentrating mainly on maize. Gene duplication events contributed to the expansion of NCS2 genes from lower aquatic plants to higher angiosperms, and whole-genome/segmental and single-gene duplication events were responsible for the expansion of the maize NCS2 gene family. Phylogenetic construction showed three NCS2 subfamilies, I, II, and III. According to homology-based relationships, members of subfamily I are NCS2/AzgA-like genes, whereas those in subfamilies II and III are NCS2/NATs. Moreover, subfamily I exhibited ancient origins. A motif compositional analysis showed that one symbolic motif (motif 4) of the NCS2/NAT genes was absent in subfamily I. In maize, three NCS2/AzgA-like and 21 NCS2/NAT genes were identified, and purifying selection influenced the duplication of maize NCS2 genes. Additionally, a population genetic analysis of NCS2 genes revealed that ZmNCS2–21 showed the greatest diversity between the 78 inbred and 22 wild surveyed maize populations. An expression profile analysis using transcriptome data and quantitative real-time PCR revealed that NCS2 genes in maize are involved in diverse developmental processes and responses to abiotic stresses, including abscisic acid, salt (NaCl), polyethylene glycol, and low (4°C) and high (42°C) temperatures. ZmNCS2 genes with relatively close relationships had similar expression patterns, strongly indicating functional redundancy. Finally, ZmNCS2–16 and ZmNCS2–23 localize in the plasma membrane, which confirmed their predicted membrane structures. These results provide a foundation for future studies regarding the functions of ZmNCS2 proteins, particularly those with potentially important roles in plant responses to abiotic stresses.